Refugees: Negative health consequences without the anticipated savings - Louise Biddle (DIW Weekly Report, 2024)
Refugees have limited health care entitlements during the asylum process. In February 2024, the maximum length of this exclusion period was increased from 18 to 36 months. This increase may double the actual waiting time, which is currently already more than one year, as data from the Socio-Economic Panel show. This particularly affects refugees with a low level of education and little knowledge of German. A longer waiting time not only negatively impacts the health of affected individuals but is also disadvantageous for the state; late treatment often requires more expensive treatment. Thus, shortening the period would have been more sensible than increasing it. The electronic health insurance card (EHIC) for refugees makes access to health services during this waiting period easier, as it reduces administrative barriers. However, just under 20 percent of all refugees have an EHIC, as the system has not been introduced in all federal states. The electronic health insurance card should be introduced nationwide in order to cushion the negative effects of extended restrictions on health care.
Keywords: H51; I14; J15; 330; efugees; asylum seekers; health care entitlement; health care access; health inequities